Gen Z Audience Reception of Digital Activism “Tuntutan 17+8” on Instagram - Khoirun Ni'mah; Ratih Pandu Mustikasari (Lavish Opulent Education, 2026)
The use of social media such as Instagram as a platform for expressing public aspirations, particularly through digital activism, serves as the background of this study. This research aims to analyze how Generation Z receives digital activism “Tuntutan 17+8” on Instagram by examining the role of visual aesthetics, the phenomenon of Fear of Missing Out (FOMO), as well as the influence of political background and peer environment in shaping audience engagement. This study employs a descriptive qualitative approach based on Stuart Hall’s Encoding-Decoding Reception Theory. The data were collected through in-depth interviews with seven informants selected using purposive sampling based on predetermined criteria. The findings indicate that Generation Z’s reception of digital activism “Tuntutan 17+8” on Instagram can be categorized into two positions, namely dominant-hegemonic and negotiated positions. Informants in the dominant position tend to fully accept and support the messages conveyed, as they are perceived to be relevant and effective in increasing public awareness. Meanwhile, informants in the negotiated position demonstrate a more selective attitude by accepting certain parts of the message while also criticizing aspects of its delivery that are considered inappropriate. In addition, visually appealing elements, such as the use of colors and creative design, are proven to enhance audience interest and facilitate message comprehension. The phenomenon of FOMO also plays a role in encouraging Generation Z’s participation in digital activism “Tuntutan 17+8” on Instagram, although such participation tends to be simple, such as reposting content or giving brief responses. This condition reflects a pattern of slacktivism. Nevertheless, FOMO can also have a positive impact by expanding the reach of information and increasing public awareness of the issue. Furthermore, political background and peer group influence also affect how individuals interpret and respond to messages, as they are shaped through interaction and discussion within their social environment.